THE ECONOMIC RIGHTS OF THE CITIZEN IN THE IRAQI AND IRANIAN CONSTITUTIONS DHAFER JALIL HASSAN JUNAIH AL-HUSSEINAWI (IRAQ) - Dr. Maytham Nemati (Iran) (Scholar Express Journals, 2022)
Citizen's rights are the moral principles or social norms that describe a model of human behavior that is generally understood as a set of fundamental and inviolable rights that cannot be touched and they are due and inherent to every individual simply because of being a citizen. This right is adherent to them regardless of their religion, ethnicity, or other status. Within the context of local and international legislation, their protection is structured as legal rights. The issue of citizen's rights continues to be front and center in the fields of legal, international, and constitutional studies. This concern was not limited to those working in the field of competence, but also included those interested in the citizen and his rights in general, as well as the fundamental problem and its ostensible solution. Hence, the problem of the article that we will include in the following question arises: What are the economic rights of the citizen in the Iraqi constitution and Iranian constitution? The major goal is to examine citizens' economic rights in the Iranian and Iraqi constitutions, with sub-goals including clarifying the concept of citizen rights and citizenship in the Iranian and Iraqi constitutions, examining laws related to civil rights in the Iranian and Iraqi constitutions, and examining laws that respect citizens' legitimate freedoms in these two constitutions. One of the research results is that the in-real implementation of the citizen's economic rights can be achieved in the Iraqi and Iranian constitutions without a proactive participation of governments at the local and national levels. All power must be placed in the hands of local governments to take a human rights-sensitive approach to issues of local governance and administrative subordination. It instead necessitates acknowledging the importance of local governments in the relationship between rights holders and multielement and tiered governance systems.
Keywords: citizen's rights; economic rights; Iraq; Iran